Pengaruh Total Asset Turnover dan Debt to Equity Ratio terhadap Return on Equity pada PT Hanjaya Mandala Sampoerna Tbk Periode 2014–2023 - Tri Muhtar; Waluyo Jati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2026)
This study aims to examine the effect of Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) on Return On Equity (ROE) at PT Hanjaya Mandala Sampoerna Tbk during the period 2014–2023. The method in this study is quantitative associative. The tools used in this study include classical assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests, as well as simple and multiple linear regression analysis, determination tests (R square), and hypothesis testing including t-test and F-test. The data used in this study are secondary data in the form of annual financial statements obtained from the Indonesia Stock Exchange.The results of the study indicate that partially Total Asset Turnover (TATO) has a positive and significant effect on Return On Equity (ROE), as evidenced by a t-value of 5.727 > the t-table value of 2.365, and a significance value of 0.001 < 0.05. Meanwhile, Debt to Equity Ratio (DER) partially has no significant effect on Return On Equity (ROE), with a t-value of 1.139 which is smaller than the t-table value of 2.365 and a significance value of 0.292 > 0.05.Simultaneously, Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) have a significant effect on Return On Equity (ROE), as indicated by an F-value of 17.351 > the F-table value of 4.74 and a significance level of 0.002 < 0.05.